Heavy Drinking among Women Receiving Intensive Motivational Interviewing: 6-Month Outcomes. Issue 5 (20th October 2019) - Polcin, Douglas L.; Nayak, Madhabika B.; Korcha, Rachael; Pugh, Sheila; Witbrodt, Jane; Salinardi, Michelle; Galloway, Gantt; Nelson, Emily
ABSTRACT: Compared to men, women with alcohol use disorders experience more severe consequences related to drinking. Intensive Motivational Interviewing (IMI) is a new 9-session version of Motivational Interviewing (MI) designed for women with alcohol use disorders. The current study reports outcomes from a randomized clinical trial of IMI compared to a single session of MI. Data were collected at baseline, 2-month, and 6-month follow-up. In addition to a standard "intent-to-treat" (ITT) analysis, we conducted disaggregated subgroup analyses of women who were heavy drinkers and a "per protocol" (PP) analysis of women in the IMI condition who attended 7–9 sessions (80% of the IMI sample). Women in both study conditions made large reductions in drinking between baseline and 2 months that were maintained at 6 months. Generalized estimating equation (GEE) models using the full sample (N = 215) did not show time by condition differences, but heavy drinkers(n = 153) receiving IMI showed significantly larger reductions in drinking at 2- and 6-month follow-up than the comparison condition. Assessment of heavy drinkers using the PP sample showed larger between condition differences favoring IMI at both follow-up time points. Results support the efficacy of IMI in terms of reducing drinking, particularly among women who are heavy drinkers.